Shifting the State Burden in Infrastructure Financing through the Issuance of Government Sukuk - Ima Amaliah; Tasya Aspiranti (Journal of Economics, Business, and Accountancy Ventura, 2022)
This research is intended to introduce and elaborate on the role of government sukuk as one of the macroeconomic policy instruments to cover the government budget deficit and infrastructure financing in Indonesia. This study developed an analysis model during the 2008.Q2-2020.Q4 period to show that the policy of developing Islamic financial instruments is closely related to macroeconomic variables. This study uses a dynamic linear ECM in developing government sukuk both in the short and long term. This study finds that sukuk budget deficit and infrastructure financing positively influence government sukuk issuance in the short term. While in the long term, infrastructure financing negatively influences government sukuk issuance. This study may suggest that the role of government sukuk as a substitute for foreign debt in building infrastructure must be further enhanced. The government should promote trust regarding government sukuk as a reliable investment instrument so that the government sukuk market expands and becomes an important source of financing for economic development, particularly infrastructure development.